Legal Politics and Analysis on the Extension of the Term of Office of Village Heads in Indonesia - Riyadi, Rusman; Rokhim, Abdul; Utami, Nofi Sri (Journal of Public Representative and Society Provision, 2025)
This study aims to analyze the term of office of village heads according to Law Number 3 of 2024 and examine the legal politics behind the extension of the term of office. The change in the term of office from six years and three periods to eight years and two periods has raised pros and cons in the community, as well as raised questions about the direction of national legal policy. This research uses a normative juridical approach with a descriptive-analytical method, through a literature study of laws and regulations, legal documents, and scientific literature. The results of the study show that the policy of extending the term of office of village heads is more political than based on objective evaluation. Pressure from the village head association became the dominant factor in the legislation process, which showed the strong influence of group interests in the formation of laws. In theory, this policy is contrary to the principles of power limitation and constitutional democracy. In addition, the extension of the term of office has the potential to weaken community supervision, hinder leadership regeneration, and increase the risk of abuse of authority at the village level. Thus, the extension of the term of office of the village head not only has legal consequences, but also has an impact on the quality of local democracy. A critical evaluation of the political direction of law formation is needed so that it remains based on the principles of the state of law, democracy, and the protection of the interests of the village community.